The rising home birth trend in America - Aliyev, Nurlan; Roldan, Chastidy; Cakmak, Bulent (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
In recent years home birth rates are increased in the whole world, mainly in the United States (US). Between 2004-2012, non-hospital births increasing rate is 89% in the US. Home birth increased especially among the married, non-Hispanic, over 35 years of age, multipar and singleton pregnancies. However the high rate of cesarean birth did not increase in recent years in the US, now it has been stable at 32%. It is reported that the stability of the cesarean rate is related to rising rate of home birth. In this mini review, the rising rate of home birth and its consequences in the US were discussed.